An Indonesian Adaptation of The Students’ Preparedness for University e-Learning Environment Questionnaire - Kasiyah Junus; Lia Sadita; Titin Siswantining; Diana Nur Vitasari (Jurnal Sistem Informasi, 2023)
Although most students are digital natives, online learning requires different skills as compared to conventional face-to-face learning. This paper aims to adapt and test the reliability and validity of the Students’ Preparedness for the University e-Learning Environment questionnaire developed by Parkes et al. into Bahasa Indonesia. The original questionnaire covers a wide range of competencies relevant to e-learning preparedness for university e-learning environments in three dimensions. Prior to reliability and validity checking, pilot testing is conducted to test the unidimesionality of the instrument and the rating scale. An item-match analysis test is also carried out to observe the suitability of each item. Then, the final version of the questionnaire is administered to a large representative sample of respondents for whom the questionnaire is intended. The results show that, with a total of 1446 students from a public university in Indonesia as respondents, the adapted questionnaire is valid and reliable.